2021
DOI: 10.3390/en14144352
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Corrosion Characteristics of Internal Combustion Engine Materials in Second-Generation Jatropha Curcas Biodiesel

Abstract: The corrosiveness of biodiesel affects the fuel processing infrastructure and different parts of an internal combustion (IC) engine. The present study investigates the corrosion behaviour of automotive materials such as stainless steel, aluminium, cast iron, and copper in 20% (B20) and 30% (B30) by volume second-generation Jatropha biodiesel using an immersion test. The results were compared with petro-diesel (B0). Various fuel properties such as the viscosity, density, water content, total acid number (TAN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The high corrosion resistance in stainless steel might be due to the carbon content (0.98 % by weight) in its composition [72] . As can be observed, in comparison with other metals copper was more prone to corrosion owing to its high weight loss (8 mg in B50 blend) [73] . Enzhu et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high corrosion resistance in stainless steel might be due to the carbon content (0.98 % by weight) in its composition [72] . As can be observed, in comparison with other metals copper was more prone to corrosion owing to its high weight loss (8 mg in B50 blend) [73] . Enzhu et al.…”
Section: Resultsmentioning
confidence: 99%
“…[72] As can be observed, in comparison with other metals copper was more prone to corrosion owing to its high weight loss (8 mg in B50 blend). [73] Enzhu et al reported the high corrosion in copper was due to its easy oxidation, which leads to formation of metal oxides (CuO, Cu 2 O). [74] The corrosion rate of zinc was higher than aluminium and galvanized steel in blends and B100.…”
Section: Corrosion Analysis Of Wfobdmentioning
confidence: 99%
“…Biodiesels are associated with corrosive elements which affect the different parts of the internal combustion engine. Shahabuddin et al [31] investigated the corrosion performance of automotive component materials like cast iron, copper and stainless steel in varying volume concentrations of Jatropha biodiesel via immersion test. Fuel properties like oxidation stability, total acid content, viscosity, density and water content were analysed by scanning electron microscopy and optical microscopy to check the corroded parts' morphology.…”
Section: Corrosion Study Of Internal Combustion Engine Materials In V...mentioning
confidence: 99%
“…Concentrated efforts have been made to reduce the usage of fossil fuels after ascertaining their adverse contributions to climate change and pollution [1]. The automotive industry still largely relies on internal combustion engines fueled by diesel [2]. However, fuel cells and batteries are becoming viable alternatives to diminish and also control the localization of pollutant emissions [3].…”
Section: Introductionmentioning
confidence: 99%